2022
DOI: 10.2460/javma.21.03.0152
|View full text |Cite
|
Sign up to set email alerts
|

Manual plasma exchange to treat an accidental overdose of intravenous lipid emulsion in a dog with baclofen toxicosis

Abstract: CASE DESCRIPTION An approximately 2-year-old sexually intact male German Shorthair Pointer was presented for treatment of baclofen toxicosis. CLINICAL FINDINGS The dog had signs of severe baclofen toxicosis (no gag reflex, intermittent vocalization, and stupor) and received intravenous lipid emulsion (142 mL/kg) as a constant rate infusion over 11 hours. Severe hypertriglyceridemia (29,221 mg/dL; reference interval, 19 to 133 mg/dL) developed, followed by cardiovascular depression (poor peripheral perfusion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…17 Although no adverse effects attributable to lipid therapy were noted in this case report, adverse effects reported in veterinary medicine include hypertriglyceridemia, pancreatitis, coagulation disturbances, intraocular lipid deposits, and respiratory distress. 4 The severe hypocalcemia reported in this case is likely the cause of CPA given the exposure to citrate, severe sinus bradycardia, lack of calcium supplementation during TPE, and return of spontaneous circulation after calcium gluconate administration, although the severity of bifenthrin toxicosis could also have caused CPA. Bunker et al 18 reported cardiac arrest in dogs after IV citrate administration, with ionized calcium concentrations ranging from 0.16 to 0.55 mmol/L.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…17 Although no adverse effects attributable to lipid therapy were noted in this case report, adverse effects reported in veterinary medicine include hypertriglyceridemia, pancreatitis, coagulation disturbances, intraocular lipid deposits, and respiratory distress. 4 The severe hypocalcemia reported in this case is likely the cause of CPA given the exposure to citrate, severe sinus bradycardia, lack of calcium supplementation during TPE, and return of spontaneous circulation after calcium gluconate administration, although the severity of bifenthrin toxicosis could also have caused CPA. Bunker et al 18 reported cardiac arrest in dogs after IV citrate administration, with ionized calcium concentrations ranging from 0.16 to 0.55 mmol/L.…”
Section: Discussionmentioning
confidence: 71%
“…The postmortem analysis was performed using gas chromatography-mass spectrometry, which confirmed high concentrations of bifenthrin in the liver and kidney. 1 Epstein et al 4 performed manual TPE on a patient with an iatrogenic intralipid emulsion overdose in an attempt to treat the patient's baclofen toxicosis. They saw no appreciable decrease in plasma baclofen concentrations, but their method was highly successful in removing intralipids by documenting a decrease in serum triglycerides by more than 77%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations